Tongues Untied (Marlon Riggs, 1989) et Paris is Burning (Jennie Livingston, 1990) : les documentaires du New Queer Cinema - Camille Bui (Revue LISA)
In the early nineties, American film critic B. Ruby Rich welcomed the birth of what she called “new queer cinema” — a wave of independent gay, lesbian, and transgender films by and large well-received at film festivals. At a time when gay activism matured, queer cinema blended political and aesthetic concerns. Among these films, Tongues Untied (1989) by Marlon T. Riggs and Paris is Burning (1990) by Jennie Livingston link the notion of identity with race, class and gender. In the light of Judith Butler’s definition of gender as performative, this article discusses how these films try to destabilize the gender norms of American society by questioning the traditional image of Black Americans conveyed by mainstream movies. The two films give new visibility to marginalized communities of Black and Latino gays and transgenders, thus opening the field of possible identities. Yet they differ strikingly at the formal level. Whereas M. Riggs proposes an essay film, thus doing away with cinematic realism, Livingston adopts a more classic style, close to ethnographic documentary. By analyzing the documentary poetics of the two films, this paper intends to show how the filmmakers develop different strategies of resistance against the “technologies of gender.”